(untitled) (El Hilo de la Fabula, 2020)
The Borges’s story «Ibn–Hakam al–Bokhari, Murdered in His Labyrinth» was first published in magazine Sur in 1951 and included in the second edition of El Aleph in 1952. Borges’s nephew Miguel de Torre Borges published the final page and a half of the manuscript of the story in his book of family photographs and manuscripts. That fragment is studied here in depth using the techniques of genetic criticism, along the lines explored in How Borges Wrote (2018).